Atom Probe Analysis of a Zr-based Bulk Metallic Glass. (August 2022) - Bilal, Huma; Nomoto, Keita; Gludovatz, Bernd; Kruzic, Jamie J.; Ceguerra, Anna V.; Ringer, Simon P.
Abstract: Abstract : Zr-based bulk metallic glasses (BMGs) are amorphous alloys that can exhibit excellent mechanical properties, including high yield strength and fracture toughness. These properties are linked to local microstructural heterogeneities. Whether via microscopy-based techniques, synchrotron techniques, or calorimetric approaches, the amorphous structure of BMGs makes the characterisation of the details of these local structural and chemical heterogeneities extremely challenging. Our focus here is on atom probe tomography (APT), where considerable uncertainty remains in terms of how and when to apply this otherwise powerful technique to amorphous materials. This work reports a systematic evaluation of the experimental parameter space. We report results of BMG composition acquired against various APT operating parameters for Zr63.96 Cu13.36 Ni10.29 Al11.04 Nb1.25 (at. %). We demonstrate that a customised peak-based ranging approach yields satisfactory compositional accuracy with absolute errors of <1 at. %. Beyond composition, we have discussed the data quality in terms of attributes of the mass spectra: mass resolution, signal-to-thermal tail ratio, and overlapped peak ratio. We also assess the composition of the well-known clustered evaporation effects, common in APT data of BMGs. We conclude that these regions have negligible differences in composition from the surrounding "matrix" or bulk in these alloys.